Penerapan Dashboard Business Intelligence untuk Meningkatkan Penjualan Mobil: Studi Kasus pada Perusahaan XYZ - Muhammad Rohid Nur Fajrian; Githriff Ahmad Nibross Vroticca; Ainur Rifki Pratama; Ma’had Wicaksono (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
The automotive industry is a strategic sector that plays a crucial role in national economic growth. Facing rapid digital transformation, automotive companies are increasingly adopting Business Intelligence (BI) systems to facilitate a data-oriented decision-making process. This study aims to explore the implementation of BI in XYZ, one of Indonesia’s largest car manufacturers. Using a descriptive qualitative approach through literature review, the research highlights how BI dashboards enable real-time analysis of vehicle sales trends, regional performance, and product models. The findings indicate that BI significantly enhances strategic planning, marketing accuracy, and operational efficiency. Visual tools such as Tableau provide centralized dashboards that facilitate faster insights, enabling companies to adjust production and distribution strategies based on data patterns. The study concludes that BI is not merely a visualization tool but a vital element of the digital transformation strategy in the automotive sector.